Coupled CFD-DEM simulation of granular LCM bridging in a fracture. (2nd April 2020) - Zhu, Baiyu; Tang, Hongming; Wang, Xi; Zhao, Feng; Yuan, Xuefang
Abstract: Developed fractures are important storage space and permeable channel in hydrocarbon reservoirs. However, they will lead to drill-in fluid loss and induce severe formation damage. Fracture plugging with granular lost circulation material (LCM) is most commonly used to control drill-in fluid loss. To our best knowledge, traditional research about LCM bridging mainly performed by the trial-and-error method. However, the behavior of granular LCM migration and bridging in a fracture on mesoscale is still unclear. In this paper, the coupled CFD-DEM approach is used to simulate the flow of granular LCM in a vertical fracture. The effects of particle size distribution (PSD) and concentration on the fracture plugging process are studied by a series of controlled numerical experiments. The research suggests that: (1) When Wf /D50 <1.5, the critical particle concentration softly increases with particle size distribution (PSD), but the area with Wf /D50 >1.5 the critical particle concentration sharply increases with PSD. (2) The plugging process can be divided into two distinct stages from pressure drop rate: particle bridging and particle accumulation. (3) The drill-in fluid loss rate is affected by the plugging process, the structure of plugging zone and PSD.